Impact of new teacher recruitment policies on development of educational systems in sub-Saharan Africa - (:unkn) unknown (My University, 2014)
The development of Education systems in Sub-Saharan Africa as a whole and specially in Burkina Faso, Congo, Senegal shows ups and downs due to their low development, despite commitments made by the international community in 1990 at Jomtien in Thailand. The Dakar Forum in 2000, while recognizing progress recorded since independence for African countries,highlighted the need for States to undertake deep reforms with regard to education systems. Actually, since independence, the will shown by States to grant priority to education - as they are convinced that education has a positive impact on development of nations - was undermined by a number of uncertainties, including Structural Adjustment Programs in the 1990’s, which have been limiting factors in education systems development. Consequently, education systems weremaintained through a number of strategies aiming at increasing education opportunities in situations where there was almost no financial investment. Recommendations from the Dakar Forum targeting the adoption of education development policies helped to address the most important expenditure line in education budget, i.e. the wage bill. Therefore, appealing to new types of teachers or Non-Government teachers is becoming widespread and is emerging as a standard, thereby deregulating the teaching profession formerly built. After reviewing developments in education system within three countries, from independences to the 2000’s, we analyzed the background in which new types of teachers emerged before showing their contribution to education systems development, both in terms of quantity and quality. This analysis was conducted following a methodology consisting in reviewing documents and using several databases of the Education Systems Analysis Program of CONFEMEN (PASEC), the Evaluation of Learning Achievement (EAS) and the Southern and Eastern Africa Consortium for Monitoring Education Quality (SACMEQ). At the end of our research, we have r
Keywords: African Research